Pola Pendidikan Islam Berbasis Tazkiyah Al-Nafs Bagi Lansia Untuk Meraih Nafs Al-Muthmainnah - Muhammad Rusmin Chaedar (Syifa al-Qulub, 2021)
The aging is one of natural life process would be faced by every human being, and the elderly stage is the most crucial process in their life. In this stage, humans naturally experience a change condition, such as  physical, psychological and social change in relating to another. The elderly also suffer from anxiety and worry. They realize that death is getting closer and more aware of their need for religion, so, they become more active in studying Islam. Islamic education and learning for the elderly requires a certain pattern, because the main purpose of religious learning for them is to achieve peace and tranquility of the soul (nafs muthmainnah). The aims of this study is for determining:  The goal of providing Islamic education for those who are elderly; The pattern of Islamic education for the elderly based on purification of the soul (tazkiyah al-nafs). The research approach in this study used a qualitative, meanwhile, the research method used a literature study. This research resulted in following: The elderly in perspective of Islamic education are still have obligation to seek knowledge. One of main goals in providing an Islamic education for elderly is to get hold of the soul. While the general patterns in implementation of Islamic education for elderly are: 1) The general approach in educating and learning is through tazkiyah al-nafs, which at a practical level used approaches of: habituation, giving advice, exemplary, story; 2) The Islamic education materials provided in learning process for elderly are purification of akidah, worship, morals, stories and practice to smooth heart through dhikr to Allah (dhikrullah), prayer, reading the Qur`an, etc. 3) The methods in implementing of Islamic education and learning through lectures, stories, questions and answers, demonstrations, exemplary and memorization methods. 4). The media and facilities must be comfortable and adapted to the conditions of elderly, 5) The teachers must have good character and role model; 6) The students (elderly) must have sincere intentions and sincerity.